Production of secondary metabolites in stirred tank bioreactor co-cultures of Streptomyces noursei and Aspergillus terreus - Boruta, Tomasz; Ścigaczewska, Anna; Bizukojć, Marcin (Frontiers in Bioengineering and Biotechnology, 2022)
The focus of the study was to characterize the bioprocess kinetics and secondary metabolites production in the novel microbial co-cultivation system involving Streptomyces noursei ATCC 11455 (the producer of an antifungal substance known as nystatin) and Aspergillus terreus ATCC 20542 (the source of lovastatin, a cholesterol-lowering drug). The investigated “A. terreus vs. S. noursei” stirred tank bioreactor co-cultures allowed for the concurrent development and observable biosynthetic activity of both species. In total, the production profiles of 50 secondary metabolites were monitored over the course of the study. The co-cultures were found to be effective in terms of enhancing the biosynthesis of several metabolic products, including mevinolinic acid, an acidic form of lovastatin. This work provided a methodological example of assessing the activity of a given strain in the co-culture by using the substrates which can be metabolized exclusively by this strain. Since S. noursei was shown to be incapable of lactose utilization, the observed changes in lactose levels were attributed to A. terreus and thus confirmed its viability. The study was complemented with the comparative microscopic observations of filamentous morphologies exhibited in the co-cultures and corresponding monocultures.